A multiscale analysis of Gray Vireo (Vireo vicinior) nest-site selection in central New Mexico - Jonathan P. Harris (Resilience Alliance, 2020)
There are many gaps in our understanding of Gray Vireo (Vireo vicinior) life history especially as it relates to nesting ecology. Our objective was to determine habitat features selected by Gray Vireos for nesting to improve management strategies for breeding populations. We searched for Gray Vireo nests on Kirtland Air Force Base in Albuquerque, New Mexico from 2016 to 2017. We estimated Gray Vireo nest-site selection at the tree level, the surrounding vegetation, and at two broader scales corresponding to selection within territories. Nest-site selection was estimated for 99 Gray Vireo nests. For tree-level selection, we compared characteristics of nesting trees with mean characteristics from groups of six randomly selected one-seed junipers (Juniperus monosperma) within a 25-m radius. We also compared overall vegetation characteristics at the 25-m scale for nesting plots and 66 randomly selected plots. Broad-scale cover proportions of nest sites and random points were estimated at 50- and 100-m radius spatial scales using a geographic information system. Gray Vireos selected nesting trees that were taller and wider than other adjacent junipers. Selection of vegetation characteristics surrounding nests showed a similar pattern, where Gray Vireos nested in areas where junipers were taller, wider, and had greater foliage density than was randomly available. Broad-scale analyses suggested that Gray Vireos selected nest sites in areas with higher proportions of junipers at low elevations (< 1954 m), and lower proportions of junipers in higher elevations (> 1954 m); however, juniper proportions at nest sites consistently ranged from 15 to 30% of available cover. Gray Vireos also tended to select areas with less pinyon pine than what was randomly available at the 100-m radius scale. Future management strategies should provide large patches of old-growth juniper to optimize Gray Vireo nesting habitat.